The Role of Ambulatory Care Pharmacists in an HIV Multidisciplinary Team within a Free and Bilingual Clinic - Ann M. Fugit, Pharm.D., BCPS; Sallie D. Mayer, Pharm.D., MBA, BCPS, CDE; Radha S. Vanmali, Pharm.D., BCACP (University of Minnesota Libraries Publishing, 2013)
Objective: Describe the role and integration of ambulatory care pharmacists in a Human Immunodeficiency Virus (HIV) clinic within a free and bilingual clinic with regards to types of interventions made during the patient-pharmacist visit. Design: Retrospective, single-centered, chart review. Setting: Free, bilingual clinic in Richmond, VA. Participants: Thirty-two adult patients with diagnosed HIV receiving care in the clinic between June 30, 2010 and January 26, 2011. Main Outcome Measure: Types of interventions documented during the patient-pharmacist visit, categorized as medication review, patient education, or adherence monitoring. Results: Total of 32 patients accounted for 55 patient-pharmacist visits and 296 interventions. The most common interventions were medication review (66.9%), patient education (23.3%), and adherence monitoring (9.8%). Post-hoc analysis suggests Hispanic patients are more likely to be diagnosed with Acquired Immune Deficiency Syndrome (AIDS) (P = 0.01), have current or history of opportunistic infection (OI) (P=0.01), and have current or history of OI prophylaxis (P = 0.03). Adherence monitoring was less common amongst the non-Hispanics (7.1%) compared to the Hispanic sub-population (16.5%), (P = 0.04). Conclusion: The role of ambulatory care pharmacists in a free and bilingual clinic goes beyond adherence monitoring. Pharmacists can be a valuable part of the patient care team by providing medication review and patient education for HIV and other co-morbidities within free clinics. Further research is warranted to assess outcomes and to further explore the underlying barriers to early HIV diagnosis and adherence within the Hispanic population.